Boundary Layer under Oscillatory Wave. (18th August 2011) - Adityawan, Mohammad Bagus; Tanaka, Hitoshi
Abstract : Turbulence due to wave motion and propagation is a very important aspect in sediment transport modeling. The boundary layer characteristic during the process will highly influence the sediment transport mechanism at the bottom. 1D model approach has been widely used to assess the turbulent boundary layer. However, the need for a more detailed model leads to the development of a more sophisticated models. This study presents a 2D turbulent model usingk - ω equation to approach the turbulent boundary layer characteristic in oscillatory wave. The equations are solved using finite-difference center scheme. The model is applied to the case of oscillatory sinusoidal and skew wave. The velocity profile and bed stress were compared to those obtained from wind channel experimental data and 1Dk - ω model from previous study.